NOUN PHRASES TRANSLATION IN "METAMORPHOSIS" NOVELLA BASED ON VENUTI'S TRANSLATION STRATEGIES THEORY - Utama, Iftar Puja (2015)
The research entitledNoun Phrases Translation in Metamorphosis Novella Based on Venuti's Translation Strategiesaims to classify types of noun phrases in the Metamorphosis novella,identify the specific translation strategiesand investigate the professional translator'sreasons behind the use of that translation strategies via interview. The research uses a qualitative approach and descriptive analysis method in obtaining and analyzing the specific translation strategies (Jacob, 1998; Maxwell, 1996)and alsoquantitative approach to describe the percentage of noun phrases and translation strategies category (Lohr, 1999). The results of the research show that there are nine types of noun phrase found in theMetamorphosis novella and nine translation strategies were applied by the professional translator. The research also shows that there is a correlation between the result of the data analysis with the answer of the professional translator which explains that the professional translator tends to use domestication strategy. Based on interview data, the results indicate that there are severaladvantages and weaknesses of being a translator who tends to use domestication translation strategy. The advantages are: (1) The reader can more easily understand the story of the novella. (2) Although the novel is not a local product but many aspects of local cultures can be included in the novella. (3) The readers will feel that the translation is more natural.On the contrary, the weaknesses of a translator who tends to use domestication translation strategy are: (1) The novella becomes less imaginative. (2) The cultural aspects in the source language are being paled. (3) There will be a huge 'gap'between the terms in source language and the target language if the translator is not translate it correctly. Keywords: Noun Phrase, Translation Strategies, Venuti Penelitian yang berjudul Noun Phrases Translation in Metamorphosis Novella Based on Venuti's Translation Strategies bertujuan untuk mengklasifikasikan jenis frasa nomina dalam novelaMetamorphosis, mengidentifikasi strategi penerjemahannya, dan menyelidiki alasan dibalik penggunaan strategi terjemahandaripenerjemahprofesional melalui wawancara. Penelitian ini menggunakan pendekatan kualitatif dan metode analisis deskriptif dalam memeroleh dan menganalisis strategiterjemahan (Jacob, 1998; Maxwell, 1996) dan juga pendekatan kuantitatif untuk menggambarkan persentase frasa nomina dan kategoridaristrategiterjemahan (Lohr, 1999). Hasil penelitian menunjukkan bahwa ada sembilan jenis frasanominadan sembilan strategi penerjemahan diterapkan oleh penerjemah profesionaldalam novellaMetamorphosis. Hasil penelitian juga menunjukkan bahwa ada korelasi antara hasil analisis data dengan jawaban dari penerjemah profesional yang menjelaskan bahwa penerjemah profesional cenderung menggunakan strategi domestikasi. Berdasarkan datahasildari wawancara, hasil menunjukkan bahwa ada beberapa keuntungan dan kelemahan menjadi penerjemah yang cenderung menggunakan strategi penerjemahan domestikasi. Keuntungan adalah: (1) Pembaca dapat lebih mudah memahami cerita novel tersebut. (2) Meskipun novel ini bukan produk lokal tetapi banyak aspek budaya lokal dapat dimasukkan dalam novel tersebut. (3) Para pembaca akan merasa bahwa terjemahan lebih alami. Sebaliknya, kelemahan dari penerjemah yang cenderung menggunakan strategi terjemahan domestikasi adalah: (1) novel tersebut menjadi kurang imajinatif. (2) aspek budaya dalam bahasa asalakanmemudar. (3) Akan ada 'jarak' antara istilah dalam bahasa sumber dan bahasa target jika penerjemah tidak menerjemahkan dengantepat. Kata kunci: Frasa Nomina, Strategi Penerjemahan, Venuti